Pre-Learning Supervision Evaluation: Integration of 4Cs and 21st Century Graduate Profile Dimensions - Winaryati, Eny; Munsarif, Muhammad; Junaedi, Iwan; Utomo, Utomo; Arianty, Alya Dwi; Khoirunisa, Asiva; Ibrahim, Kafitra Marna (International Journal of Learning, Teaching and Educational Research, 2026)
The 21st century education requires the mastery of critical thinking, creativity, communication, and collaboration (4Cs) skills integrated into instructional practices. The research findings indicate that the implementation of 4Cs in Lesson Plans (Rencana Pelaksanaan Pembelajaran/RPP) remains suboptimal, both in terms of the equitable distribution of indicators and their alignment with graduate profile dimensions. This condition highlights the importance of in-depth evaluation at the pre-instructional stage to assess the readiness of lesson plans in supporting twenty-first-century competencies. The novelty of this article lies in offering a comprehensive evaluative approach to lesson plans on the topic of Redox Reactions, emphasizing the integration of 4Cs skills and eight graduate profile dimensions. A systematically developed supervision matrix instrument was employed, encompassing document components, learning objectives, instructional strategies, assessment, learning media, and classroom management, thereby providing a holistic overview of lesson plan readiness. The objectives of this study were: (1) to evaluate the pre-instructional stage through analysis of lesson plans on Redox Reactions with a focus on the integration of 4Cs and graduate profiles, and (2) to assess lesson plan readiness in supporting effective, contextual, and competency-oriented twenty-first-century learning. This study employed a descriptive qualitative approach with senior high school (SMA/MA) chemistry lesson plans as the research object. Data were collected using several triangulation techniques, including document analysis, indirect observation, and evaluator source triangulation. The results indicate that instructional planning was developed comprehensively and aligned with Problem-Based Learning (PBL), Understanding by Design (UbD), 4Cs, and the Pancasila Student Profile; however, it still requires strengthening through the explicit inclusion of Learning Outcomes (Capaian Pembelajaran/CP) and the completion of reflective documents such as teacher journals. Recommendations. Teachers are advised to strengthen the explicit inclusion of Learning Outcomes within the Teaching and Learning Flow (Alur Tujuan Pembelajaran/ATP) to clarify the relevance between objectives and expected achievements, as well as to incorporate teacher journals as a medium for continuous reflection. In addition, the explicit articulation of 4Cs skills and Pancasila Student Profile dimensions in lesson plan documents should be reinforced to ensure more directed instructional implementation. https://doi.org/10.26803/ijlter.25.2.22